Understanding Arabic-speaking skill learning strategies among selected Malay learners:a case study at the International Islamic University Malaysia(IIUM) - Ahmed Mohamed, Ismaiel Hassanein (Clute Institute Colorado, 2010)
In Malaysia, studies have shown that most Malay learners learning Arabic Language exhibit weak Arabic speaking skill despite spending years of learning the language. However, given the same learning environment and experience, some of them could be considered as good Arabic speakers as revealed by the results of Arabic Placement Test conducted by the Center of Languages and pre-Academic Development (CELPAD) of the International Islamic University Malaysia (IIUM). These learners have successfully scored band 7 and above in Arabic speaking skill test. The researchers believe that being aware of certain learning strategies in enhancing their speaking skills would help these learners to become good Arabic speakers. This assumption is based on several theories in language learning strategies which postulate that learners’ success in language learning or lack of it is attributable to the various strategies which different learners bring to tasks and not solely relying on environment per say. Therefore this study attempts to understand the assumption by investigating the Arabic speaking skill learning strategies of selected Malay good Arabic speakers and Malay poor Arabic speakers at the (IIUM) within and outside the parameters of the educational settings. In addition, the research also seeks to explore the students’ perception on Arabic speaking skill in terms of the importance of Arabic speaking skill for the Malay learners, the required level of Arabic speaking skill for the Malay learners and the prerequisites to become good Arabic speakers.